(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper’s research focuses on areas related to the electrical power system (EPS) used for nanosatellite platforms with an adapted electrical architecture and an effective control strategy. An overview of the relevant maximum power point tracking (MPPT) algorithms is presented towards proposing a more suitable control technique. The main contribution of this research is the implementation of a novel fuzzy logic control (FLC) strategy, which significantly reduces ripples around Maximum Power Point (MPP) improving both the efficiency and the flexibility of convergence, and the response time as well. A comparative study and analysis are presented to demonstrate the performance and the effectiveness of the proposed FLC. The assessment is performed in comparison between the most common methods (perturb and observe (P&O) and Incremental Conductance (INC)) used for MPPT. The results obtained are very substantial and show that the proposed FLC technique, with regard to the other techniques discussed in this paper, points to the extraction of the highest and most stable amount of average power under different space environmental conditions.